The impact of diffusive migration on ecosystem stability. (September 2015) - Pal, Nikhil; Samanta, Sudip; Chattopadhyay, Joydev
Abstract: In the present paper, we investigate the stability of two non-identical ecological systems, which are spatially separated, but connected through migration. We assume that the population distributions in two different patches are governed by Hastings–Powell and Upadhyay–Rai models, respectively. We also assume that all the populations are free to migrate from one patch to another. The migration and its direction are regulated by the population densities. Here, we consider that the direction of the diffusive migration is bi-directional. We propose and analyze the coupled system. Our results suggest that increase in the rate of migration can stabilize the ecosystems, which are chaotic in isolation. Extensive numerical experiments are performed to illustrate the rich dynamics of the coupled system.